DOCUMENTATION THROUGH THE USE OF DIGITAL TECHNOLOGIES IN EDUCATIONAL PRACTICE - Duška Pešić; Mirjana Nikolić; Isidora Korać (Istraživanja u Pedagogiji, 2025)
The application of digital technologies in the documentation process can enhance the visibility of learning processes, provide opportunities for (self-)reflection among various actors in the educational process, and serve as a foundation for considering further possibilities for improving the quality of practice. This paper presents the findings of a study aimed at determining how preschool teachers—students enrolled in master’s studies—assess their personal competencies in using digital technologies for documentation, which tools they use, and what additional support they need in this domain. The study involved 116 preschool teachers—students of the Professional Master’s program in Early Childhood Education at the College of Vocational Studies – Sirmium in Sremska Mitrovica—who are employed in various preschool institutions across the Republic of Serbia. A mixed-methods approach was applied. For the quantitative part of the study, a questionnaire was designed. The qualitative part included a focus group interview with 24 students from the total sample. The results show that only a small number of participants rated their competencies in using digital tools as good, even though most reported being familiar with Microsoft Office and Google tools. Almost all master’s students expressed a strong need for additional training, particularly in areas such as creating electronic portfolios and using specific digital tools. The research findings provide guidelines for developing training programs for preschool teachers in the area of digital pedagogical documentation, as well as for improving the curriculum of the Professional Master’s program in Early Childhood Education.